2014
DOI: 10.1161/hypertensionaha.113.02647
|View full text |Cite
|
Sign up to set email alerts
|

Variations of MicroRNAs in Human Placentas and Plasma From Preeclamptic Pregnancy

Abstract: Abstract-Preeclampsia is a major cause of maternal and fetal mortality and morbidity worldwide. The differential expression of several microRNAs (miRNAs) has been found in preeclamptic placentas. However, great conflict exists regarding this aspect, and detailed examinations have largely been lacking of miRNA profiles in different parts of the placenta and in maternal plasma of women with this disorder. In this study, a total of 9 downregulated miRNAs (miR-195, miR-223, miR-218, miR-17, miR-18a, miR-19b1, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
192
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(214 citation statements)
references
References 36 publications
21
192
0
Order By: Relevance
“…A great number of differentially expressed miRNAs have been identified in preeclamptic placentas, [15][16][17] and some of these differentially expressed miRNAs were demonstrated to participate in the regulation of various placental cell events and functions. [18][19][20] On the basis of these data, we speculate that the abnormally elevated androgen in PE patients may upregulate miR-22 expression in placental trophoblasts, which may target and repress ERα and aromatase and, accordingly, exacerbate the imbalanced production of androgen and estrogen in patients.To address this assumption, we examined the differential production of miR-22, 17β-HSD3, and aromatase in severe PE placentas. The effects of testosterone on miR-22, aromatase, and ERα expression, as well as estradiol production, were explored in the human trophoblastic cell line JEG-3.…”
mentioning
confidence: 86%
“…A great number of differentially expressed miRNAs have been identified in preeclamptic placentas, [15][16][17] and some of these differentially expressed miRNAs were demonstrated to participate in the regulation of various placental cell events and functions. [18][19][20] On the basis of these data, we speculate that the abnormally elevated androgen in PE patients may upregulate miR-22 expression in placental trophoblasts, which may target and repress ERα and aromatase and, accordingly, exacerbate the imbalanced production of androgen and estrogen in patients.To address this assumption, we examined the differential production of miR-22, 17β-HSD3, and aromatase in severe PE placentas. The effects of testosterone on miR-22, aromatase, and ERα expression, as well as estradiol production, were explored in the human trophoblastic cell line JEG-3.…”
mentioning
confidence: 86%
“…These include fetal weight restriction and low fetal birth weight (intrauterine growth retardation or IUGR), [81][82][83][84] toxin exposures such as environmental toxins, 85,86 cancer (hepatocellular carcinoma), 87 diabetes mellitus 88 and, the most heavily studied, human pre-eclampsia. 79,[89][90][91][92][93][94][95][96] Many of the pre-eclampsia studies have investigated miRNA expression using high throughput microarray, and qPCR (primarily in order to validate specific microarray findings). Previous studies have established that oxygen tension is implicated in placental development in humans and mice.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 99%
“…for preeclampsia. 23,25 Despite these findings, the details of the role played by miR-210 in preeclampsia development remain largely unknown. …”
mentioning
confidence: 99%
“…21,22,25 Until now, functional studies on miR-210 have mainly focused on its role in cancer. The reasons that miR-210 attracted our attention in the study of placenta development were as follows: (1) In our previous study, we found that the levels of miR-210 increased in the plasma of preeclamptic individuals early in gestation (15-18 weeks), 25 indicating its possible participation in the cause of preeclampsia at early gestation. (2) Target prediction results show that KCMF1 is one of the possible targets of miR-210, and the predicted binding site in the 3′-UTR of KCMF1 mRNA is evolutionarily conserved from amphibians to humans.…”
mentioning
confidence: 99%